2007
DOI: 10.1172/jci32994
|View full text |Cite
|
Sign up to set email alerts
|

Probing cell type–specific functions of Gi in vivo identifies GPCR regulators of insulin secretion

Abstract: The in vivo roles of the hundreds of mammalian G protein-coupled receptors (GPCRs) are incompletely understood. To explore these roles, we generated mice expressing the S1 subunit of pertussis toxin, a known inhibitor of G i/o signaling, under the control of the ROSA26 locus in a Cre recombinase-dependent manner (ROSA26 PTX ). Crossing ROSA26 PTX mice to mice expressing Cre in pancreatic β cells produced offspring with constitutive hyperinsulinemia, increased insulin secretion in response to glucose, and resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
247
3
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 167 publications
(262 citation statements)
references
References 44 publications
9
247
3
3
Order By: Relevance
“…Instead, we found that in Xenopus oocytes TAAR1 directly activates Kir3 channels via PTX-insensitive G-proteins, most likely G s proteins. This challenges an earlier report failing to demonstrate TAAR1 coupling to Kir3 channels (24). Our data reinforce that GPCRs coupled to G proteins other than G i/o can gate Kir3 channels (25)(26)(27)(28)(29).…”
Section: Discussioncontrasting
confidence: 49%
“…Instead, we found that in Xenopus oocytes TAAR1 directly activates Kir3 channels via PTX-insensitive G-proteins, most likely G s proteins. This challenges an earlier report failing to demonstrate TAAR1 coupling to Kir3 channels (24). Our data reinforce that GPCRs coupled to G proteins other than G i/o can gate Kir3 channels (25)(26)(27)(28)(29).…”
Section: Discussioncontrasting
confidence: 49%
“…To answer this question, we expressed the Gα i/o signaling inhibitor pertussis toxin (PTX) in β cells by crossing ROSA-PTX knockin mice to ePet1-cre transgenic mice (islet-PTX mice) (18,24). These animals responded to a glucosetolerance test with lower blood glucose elevations and markedly increased glucose-stimulated insulin secretion ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, also T1AM has a complex pharmacodynamic profile, being considered a multi-target molecule since amine interaction at several Gprotein-coupled receptors including trace amine-associated receptors (TAAR1 and 8; Scanlan et al, 2004;Mühlhaus et al, 2014), α2 (Regard et al, 2007;Dinter et al 2015a), β2 adrenoreceptors (Dinter et al, 2015b) and ion channels (Lucius et al, 2015) have been reported. Until now, none of these targets has been recognized to be involved in the behavioral effects of low T1AM doses, including memory stimulation and hyperalgesia.…”
Section: Introductionmentioning
confidence: 99%